An evaluation of the economics and productivity of fully mechanised tree seedling planting in Brazil - Sebastiao Guerra, Saulo Philipe [UNESP]; Soler, Rafael Ribeiro [UNESP]; Sereghetti, Guilherme Correa [UNESP]; Oguri, Guilherme (Natl Inquiry Services Centre Pty Ltd, 2019)
From an economic point of view, Eucalyptus is the most important forest genus in Brazil, covering more than 5 million ha. However, most of the silvicultural practices have a low level of mechanisation compared with harvesting and logging operations. This study presents an evaluation of the economics and productivity of the first Brazilian experience of using a planter device attached to an excavator boom while performing eucalypt seedling planting. A classic time-and-motion study was performed on two commercial tree spacings to evaluate the economic efficiency. Considering the final cost of planted seedlings, the wider spacing was 17% higher than narrower spacing, due to a higher productivity: 355 and 324 seedlings per productive machine hour (pmh), respectively. Total cost was 66.84 Euro pmh(-1) and 0.21 Euro planted seedling(-1) with wider spacing.
Keywords: cost; Eucalyptus; planter; productivity